2015
DOI: 10.1002/jrs.4850
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Raman scattering based on fabry‐perot like resonance in a metal‐cladding waveguide

Abstract: A liquid-core metal-cladding waveguide structure of millimeter scale is designed to enhance Raman signal via the excitation of Fabry-Perot-like resonance. Theoretically, an oscillating field distribution covering the whole guiding layer is generated by the multireflection at the two metal interfaces. The large detection area covers the whole sample chamber because of the oscillating nature of excited high order modes with concentrated intensity. By adding metal nanoparticles, the Fabry-Perot-like resonance can… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 22 publications
(31 reference statements)
0
5
0
Order By: Relevance
“…Yin et al reported enhanced Raman scattering based on Fabry‐Perot‐like resonance in a metal‐cladding waveguide. They found that by adding metal nanoparticles, the Fabry‐Perot‐like resonance can be combined with local surface plasmons resonance to further enhance the light‐matter interaction with the target molecules, which was also confirmed by the experimental results …”
Section: Nanomaterialsmentioning
confidence: 57%
“…Yin et al reported enhanced Raman scattering based on Fabry‐Perot‐like resonance in a metal‐cladding waveguide. They found that by adding metal nanoparticles, the Fabry‐Perot‐like resonance can be combined with local surface plasmons resonance to further enhance the light‐matter interaction with the target molecules, which was also confirmed by the experimental results …”
Section: Nanomaterialsmentioning
confidence: 57%
“…The number of guided modes increases with the waveguide thickness, and a millimeter-thickness waveguide will produce thousands of guided modes, supporting thousands of periodically distributed electric field enhancement regions, which can be applicable for sensing detection 92 and Raman enhancement. 91,[93][94][95] Uniqueness in the DMCW structures makes them different from the MCWs. First, for the relatively thick DMCW chips, the excitation of ultra-high-order modes is independent of light polarization because hundreds to thousands of resonant modes are distributed within a limited angle scanning range, making the corresponding resonant angles of TE and TM modes almost overlapping (Figure 8A,B).…”
Section: Double Metal Cladding Waveguidementioning
confidence: 99%
“…The thickness of the waveguide layer can be adjusted from a micron scale to a millimeter scale. The number of guided modes increases with the waveguide thickness, and a millimeter‐thickness waveguide will produce thousands of guided modes, supporting thousands of periodically distributed electric field enhancement regions, which can be applicable for sensing detection 92 and Raman enhancement 91,93–95 …”
Section: Wers Structure Based On Limited‐range Enhancementmentioning
confidence: 99%
“…It is demonstrated that the ultrahigh-order modes [15] excited in a symmetrical metal-cladding waveguide (SMCW) are highly sensitive to the variation of structural parameters [16] and the generated oscillating wave in the guiding layer can enhance the light-matter interaction, e.g., the Raman scattering [17] , the RGB lasing [18] , and the optical bistability [19] . By adding a thinner planar waveguide on the SMCW, the so-called double metal-dielectric-metal waveguides (DMDMW) structure is formed and the realized asymmetric Fano reflectivity curve is capable of getting giant GH shifts with a strong reflected beam intensity [20] .…”
Section: Introductionmentioning
confidence: 99%